Tuning the gating energy barrier of metal-organic framework for molecular sieving - Zhang, Xue-Wen; Zhou, Dong-Dong; Zhang, Jie-Peng (Chem, 2021)
The role of adsorbent flexibility for adsorptive separation is controversial. Here, we show that the gating action, an unconventional type of flexibility, can be used to achieve molecular sieving. Two isostructural metal-organic frameworks possessing quasi-discrete/gating pores are designed and synthesized, which allow CO2 adsorption from extremely low pressures. Adding amino group on the organic ligand strengthens intra-framework hydrogen bonding, which increases the gating energy barrier to completely block N2 and CH4 with larger sizes, giving record-high CO2/N2 and CO2/CH4 selectivities. C2 and C3 hydrocarbons larger than the pore induce pore opening at significantly different pressures implying C2H4/C2H6 and C3H6/C3H8 molecular sieving. Quantitative mixture breakthrough experiments show CO2/N2 and CO2/CH4 molecular sieving and the first example of switchable C2H4/C2H6 adsorption preference, but reveal C3H6/C3H8 co-adsorption. Computational simulation and in situ single-crystal/powder X-ray diffraction show that the absence and presence of pore opening are responsible for molecular sieving and co-adsorption, respectively. [Display omitted] •Distinguishing gating and pore-opening actions of flexible adsorbents•Tuning gating energy barrier and avoiding pore opening for molecular sieving•Molecular sieving of CO2/N2 and CO2/CH4•Role of host-guest interaction at the gating moment Molecular sieving, relying on the simple size exclusion mechanism, is ideal for adsorptive separation. While guest diffusion and molecular sieving are generally judged by pore/aperture and molecule sizes, precise determination of these parameters is impossible due to the quantum effect and unavoidable flexibility of the host-guest system. The pore-opening action, a classic type of adsorbent flexibility based on structural transformation at the equilibrium states, has been regarded as a strategy for achieving molecular sieving, but its role and performance are controversial, particularly for the co-adsorption problem. The gating action, an unconventional type of adsorbent flexibility based on transient structural variation at the non-equilibrium states, is important for guest diffusion in narrow pores but is usually overlooked. We show that the gating energy barrier can be controlled for achieving molecular sieving, and the host-guest interaction at the gating moment is also important. As a special type of framework flexibility important for guest diffusion, the gating action is controlled by the energy barrier of the transient structural transformation of the pore aperture. This work highlights the possibility of rational controlling the gating energy barrier to achieve molecular sieving, the perfect type of kinetic adsorptive separation.